Platform Merdeka Mengajar: Effective innovation solutions in Merdeka Belajar Curriculum - Labib, Muhammad Helmi; Sakinah, Ummi Kultsum; Anbiya, Bakti Fatwa (PT The Collaboration UVW, 2024)
The independent learning (Merdeka Belajar) curriculum requires teachers to be able to innovate and be creative in carrying out the learning process, so a special platform for teachers was created, namely the Platform Merdeka Mengajar (PMM) as a forum for developing teachers’ teaching potential in implementing the Merdeka Belajar Curriculum. This research aimed to describe the use of the PMM as a learning innovation solution. This research used a qualitative method with descriptive analysis through a library research approach. The findings in this research showed the PMM is an important breakthrough so that teachers can adjust to the demands of the Merdeka Belajar Curriculum. Some of the features provided in the PMM include teaching tools, student assessments, independent training, community, proof of work, and inspirational videos. With this research, it is hoped that teachers can optimally utilize the features of the platform to support innovative learning in the independent curriculum.